Oral Changes in Hospitalized COVID-19 Patients: A Cross-Sectional Multicentric Study - Radwa R. Hussein; Enji Ahmed; Asmaa Abou-Bakr; Ayman A. El-Gawish; Abou-Bakr E. Ras; Dalia M. Ghalwash (Hindawi Limited, 2023)
Background. Coronavirus disease 2019 (COVID-19) has rapidly spread over the globe, and several oral symptoms have been documented. However, it is unclear whether these lesions are the result of coronavirus infection or are secondary symptoms of the patient's systemic illness. The aim of this study was to collect data from various hospitals on COVID-19 patients with oral involvement in order to highlight different oral changes that may be manifested in those patients. Methods. This observational cross-sectional multicenter study used an online questionnaire covering oral signs and symptoms that were believed to be related to COVID-19 patients who were hospitalized in different hospitals in Egypt. Results. 94.3% of the 210 patients who participated in the current study developed oral symptoms. Altered taste sensation (56.2%), burning sensation (43.3%), and oral candidiasis (40%) were the most prevalent oral symptoms (34.4%) that were found in the studied sample. Conclusions. COVID-19 has a major influence on the oral cavity, with numerous oral symptoms that may impair quality of life. Thus, considering the need for support, pain control, and management for a better prognosis, the clinical dental evaluation of hospitalized patients with infectious diseases like COVID-19 should be addressed.